STRENGTHENING OF REINFORCED CONCRETE ROAD BRIDGES COMPOSITE MATERIALS - Savchinskiy, B. V. (Science and Transport Progress, 2010)
The article examines the issues of design and the technology of strengthening the reinforced concrete bridges made of composite materials.